“AFILIAÇÃO E TEMPORALIDADE EM UMA DISCUSSÃO SOBRE FEMINICÍDIO” - Coan, Ana Luiza Henriques (2022)
The classroom is often the space of opportunity for the occurrence of certain actions that can result in different responses to the participants of this interactional event. Also, these responses may conform to what was previously displayed in the interaction or not. In other words, certain responsive actions may (or may not) be affiliated with what was said earlier. And these responsive actions happen both verbally, that is, through the use of utterances emitted by vocal sounds, and in an embodied way, that is, through facial and gestural expressions, or even through looks, torso movements, among other possibilities. All these elements are present in a discussion that had the term femicide as its starting point. The data analyzed in this paper are part of the corpus of the Grupo Linguagem, Interação e Ethnometodologia (GLIE) and are transcribed according to the Jefferson (2004) transcription model. To also analyze the non-verbal elements present, we used the multimodal transcription (Mondada, 2018). The data and analyses present in this research show, in the light of the theoretical-methodological perspectives of Conversation Analysis and Ethnomthedology, how the students of a 6th grade elementary school class, in a municipal public school in Grande Vitória, show support or not to what was said previously - (dis)affiliation - either in a bodily or verbal way, in the same turn of the speaker or in the next turn. In this sense, this work aims not only to discuss the concepts of affiliation and disaffiliation, but how they can occur both concomitantly and subsequently. In addition, we aim to contribute to studies on gender issues in school settings, once the theme was made relevant by the participants, showing the contribution and connection between the concepts of (dis)affiliation, multimodality, temporality and gender issues.